2019
DOI: 10.1111/jir.12692
|View full text |Cite
|
Sign up to set email alerts
|

Psychological well‐being of fathers with and without a child with intellectual disability: a population‐based study.

Abstract: Background Few studies have explored the wellbeing of fathers of children with intellectual disability (ID), despite the significant role that they play in their children's lives. The current study compared fathers of children with and without a child with ID on measures of psychological well-being (life satisfaction, work-family balance and general health) and dimensions of parenting (parenting self-efficacy and parent-child closeness) and then examined whether the presence of a child with ID in the family wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…We found a significantly higher odds ratio of psychological distress and poor subjective health status among fathers of disabled compared to non-disabled children. These results are similar to a study from the UK, which finds a significant difference in general health among fathers of children with and without disabilities ( Langley et al, 2020 ). A systematic review of 20 studies of Western countries examining the mental health of fathers of children with intellectual disabilities concluded that fathers of children with disabilities are more likely to exhibit poor mental health compared to fathers in the general population ( Dunn et al, 2019 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found a significantly higher odds ratio of psychological distress and poor subjective health status among fathers of disabled compared to non-disabled children. These results are similar to a study from the UK, which finds a significant difference in general health among fathers of children with and without disabilities ( Langley et al, 2020 ). A systematic review of 20 studies of Western countries examining the mental health of fathers of children with intellectual disabilities concluded that fathers of children with disabilities are more likely to exhibit poor mental health compared to fathers in the general population ( Dunn et al, 2019 ).…”
Section: Discussionsupporting
confidence: 89%
“…Identifying and addressing poor health outcomes at an early stage among fathers is important as delay in treatment might lead to poor outcomes in both them and their children ( Yogman & Garfield, 2016 ). Fathers' well-being has often been compared with that of mothers, with relatively few studies comparing psychological well-being between fathers of children with and without disability ( Boyraz & Sayger, 2011 ; Langley et al, 2020 ). Comparison with the general child-rearing situation is important in understanding the impact of a children's disability on a fathers' health.…”
Section: Introductionmentioning
confidence: 99%
“…'lockdown'). Family socio-economic position is a key explanatory variable in driving some of the observed group differences in mental health outcomes between families of children with and without ID; for children with ID themselves (Emerson and Hatton 2007), and for their mothers (Emerson 2003), fathers (Langley et al 2020) and siblings (Hayden et al 2019). Second, there may be negative life events associated with the pandemic (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Studies also consistently show elevated levels of stress in parents of children with intellectual disability ( Arakkathara & Bance, 2019 ; MacInnes & Fraser, 2009 ; Masulani-Mwale, Kauye, Gladstone, & Mathanga, 2018 ; Phillips, Conners, & Curtner-Smith, 2017 ; Tsermentseli & Kouklari, 2019 ), both mothers ( Leung, 2019 ) and fathers ( Marsh, Brown, & Mccann, 2020 ), although those levels are related solely to the child’s disability but also other factors, both internal (such as parents’ coping) end external (such as social support), as well as the child’s internalizing and externalizing problems ( Barak-Levy & Atzaba-Poria, 2020 ; Hassall, Rose, & McDonald, 2005 ; Leung, 2019 ). Higher levels of stress in parents of children with intellectual disability put a significant strain on parents, increase the risk of mental health problems, marital problems and can impair parents’ ability to positively affect the child’s behavior, as well as decrease wellbeing and overall quality of family life ( Arakkathara & Bance, 2019 ; Azeem et al, 2013 ; Barak-Levy & Atzaba-Poria, 2020 ; Langley, Totsika, & Hastings, 2020 ).…”
mentioning
confidence: 99%